STAND UP COMEDY AS A COMMUNICATION MEDIA FOR WOMEN'S RESISTANCE TO THE PATRIARCHAL SYSTEM (CASE STUDY: STAND-UP COMEDY SAKDIYAH MARUF) - Khairani, Cahya; Alfikri , Muhammad (Laboratorium Ilmu Komunikasi Fisip UHO, 2023)
This article discusses the use of stand-up comedy as a medium of communication against women's resistance to the patriarchal system. The case study used is the comic Sakdiyah Maruf, which uses stand-up comedy to voice issues of gender equality and resistance to the patriarchal system. Qualitative research methods were used to gain an in-depth understanding of stand-up comedy as a medium for women's resistance to the patriarchal system. Research data collection techniques were carried out through document analysis. The document being analyzed is a recording of Sakdiyah Maruf's stand-up comedy performance related to the theme of women's resistance to the patriarchal system, which comes from YouTube. The data analysis technique used in this research is Roland Barthes' semiotic analysis technique. The results of the study show that stand-up comedy can be an effective communication medium in the fight for gender equality and resistance to the patriarchal system. The advantages of stand-up comedy as a medium of communication against women's resistance to the patriarchal system, among others, are that it can raise public awareness of issues of gender equality, entertain and educate at the same time, and present a woman's point of view that is different from what is usually seen in the mainstream media. In conclusion, stand-up comedy can be an effective medium of communication against women's resistance to the patriarchal system and has great potential for influencing people's attitudes and behaviors regarding the issue of gender equality.